2014
DOI: 10.1186/1471-2164-15-310
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of Helicobacter pylori plasticity zones reveals that they are integrating conjugative elements with intermediate integration specificity

Abstract: BackgroundThe human gastric pathogen Helicobacter pylori is a paradigm for chronic bacterial infections. Its persistence in the stomach mucosa is facilitated by several mechanisms of immune evasion and immune modulation, but also by an unusual genetic variability which might account for the capability to adapt to changing environmental conditions during long-term colonization. This variability is reflected by the fact that almost each infected individual is colonized by a genetically unique strain. Strain-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(94 citation statements)
references
References 43 publications
2
92
0
Order By: Relevance
“…Previous studies indicated that H. pylori has a high rate of gene recombination and unusual genetic flexibility, and those traits were considered to be helpful for the adaption to the dynamic environment [18, 19]. Even though massive virulence factors of them have been studied, the mechanisms that the essential genome components of H. pylori lead to its large scale epidemic and gastrointestinal environment adaptation within human beings remain to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that H. pylori has a high rate of gene recombination and unusual genetic flexibility, and those traits were considered to be helpful for the adaption to the dynamic environment [18, 19]. Even though massive virulence factors of them have been studied, the mechanisms that the essential genome components of H. pylori lead to its large scale epidemic and gastrointestinal environment adaptation within human beings remain to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…24 More, we found genetic segments usually associated with a tfs4c cluster in other strains belonging to hpEurope and hspWAfrica1 24 More, we found genetic segments usually associated with a tfs4c cluster in other strains belonging to hpEurope and hspWAfrica1…”
Section: Discussionmentioning
confidence: 73%
“…[15][16][17][18] Another virulence factor, dupA, has been controversially associated with duodenal ulcer development. 24 These clusters are characterized according to their gene composition and genetic sequence variation. It is believed that this cluster codes for an alternative type IV secretion system, being dupA the homolog to virB4.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations